Non-performing loans are affected by macroeconomic factors- perspective of private bank sector in Bangladesh - Ferdous, Shamima (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.